1955
DOI: 10.1111/j.1467-6494.1955.tb01170.x
|View full text |Cite
|
Sign up to set email alerts
|

Reward and Punishment as Determiners of Reminiscence Effects in Schizophrenic and Normal Subjects1

Abstract: HE EFFECTS of reward and failure upon the schizophrenic patient's performance in a \ariet> of tasks has been the focus of a recent senes of studies at Duke University These investigations have indicated that threat of failure or "punishment" increases performance deficits for the schizophrenic patient m the areas of learning, discrimination, and concept formation Under conditions of reward, however, the performance of the schizophrenic patient was comparable to that of the normal S An mterference hypothesis ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
28
1

Year Published

1957
1957
1969
1969

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 21 publications
2
28
1
Order By: Relevance
“…On the face of it these possible qualities of the high interference groups resemble clmical descriptions of compulsiveness " In general, Klein's report suggested that under stress "High-Interference" S's tended to show a more rigid task orientation, whereas the "Low-Interference" S's revealed more flexibility m their approach to a variety of tasks The analogy between the two studies is inviting, in spite of several discrepancies in design, smce the present experiment made use of a normal group of S's, presumably somewhere in between Klein's "High" and "Low-Interference" groups m personality features In size estimation behavior, the normal group of the present experiment was intermediate between the good and poor premorbid groups Although there is a tendency to value flexibility (the overestimators in Klein's study) over rigidity (underestimators) in normal persons, it is possible that the absence of rigid controls, to whatever degree it occurs, is more a liability than an asset among poorly integrated schizophrenic patients (l e , among poor premorbid patients, the overestimators in this experiment) If a translation of S's could be effected between the two procedures, it would be interesting to determine whether the poor premorbid patients exhibited even less percepttial control than did the "Low-Interference" S's of Klein's research In view of the fact that poor premorbid patients have been found to differ from normal subjects more markedly than do good premorbid patients in a number of studies (1,8), including the present research, one might suppose that the absence of suppressive perceptual controls in the poor premorbid individual is a pathological feature (much beyond the desirable flexibihty of the "Low Interference" S in Klein's study)…”
Section: Nsmentioning
confidence: 93%
“…On the face of it these possible qualities of the high interference groups resemble clmical descriptions of compulsiveness " In general, Klein's report suggested that under stress "High-Interference" S's tended to show a more rigid task orientation, whereas the "Low-Interference" S's revealed more flexibility m their approach to a variety of tasks The analogy between the two studies is inviting, in spite of several discrepancies in design, smce the present experiment made use of a normal group of S's, presumably somewhere in between Klein's "High" and "Low-Interference" groups m personality features In size estimation behavior, the normal group of the present experiment was intermediate between the good and poor premorbid groups Although there is a tendency to value flexibility (the overestimators in Klein's study) over rigidity (underestimators) in normal persons, it is possible that the absence of rigid controls, to whatever degree it occurs, is more a liability than an asset among poorly integrated schizophrenic patients (l e , among poor premorbid patients, the overestimators in this experiment) If a translation of S's could be effected between the two procedures, it would be interesting to determine whether the poor premorbid patients exhibited even less percepttial control than did the "Low-Interference" S's of Klein's research In view of the fact that poor premorbid patients have been found to differ from normal subjects more markedly than do good premorbid patients in a number of studies (1,8), including the present research, one might suppose that the absence of suppressive perceptual controls in the poor premorbid individual is a pathological feature (much beyond the desirable flexibihty of the "Low Interference" S in Klein's study)…”
Section: Nsmentioning
confidence: 93%
“…Process patients may take longer or require greater pressure to change, but the potential to change is still present (cf. Bleke, 1955;Peters, 1955;Rodnick & Garmezy, 1957;Smith, 1959).…”
Section: Discussionmentioning
confidence: 99%
“…4.3 When hospitalized populations are used as a sample reflective of psychopathology, hospitalized, non-psychopathological samples should be sought as controls, since there is some evidence to indicate that hospitalization itself has systematic (mostly deleterious) effects on some aspects of psychological functioning (cf. Bleke, 1955 ;Carson, 1958;Gladis and Wischner, 1962;Johannsen, 1961;Lang and Luoto, 1962).…”
mentioning
confidence: 99%